Analisis Kesulitan Peserta Didik Kelas V dalam Memahami Konsep Bangun Ruang d SD Muhammadiyah Nglatihan - Asna Arif Fathonah; Heru Purnomo (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to analyze various obstacles faced by fifth grade students of Muhammadiyah Nglatihan Elementary School in understanding the concept of spatial figures. This study uses a qualitative approach combined with descriptive methods to obtain an in-depth picture of the phenomenon being studied, as a basis for describing the phenomenon being studied in depth as the main analysis framework. Data collection was carried out through direct participatory observation of 15 students during the mathematics learning process. The results of the study revealed that students experienced obstacles in visualizing three-dimensional shapes, distinguishing elements of spatial figures such as sides, edges, and vertices, and applying volume and surface area formulas correctly. These difficulties are caused by the lack of use of concrete media and learning approaches that are not in accordance with the stage of students' cognitive development.